Reclamação : do comando judicial aos precedentes - Julião, Gustavo Lyrio (2018)
The study examines the Brazilian writ called “Complaint” or “Reclamação”, specifically to "guarantee the authority of judicial decisions", hypothesis provided in the Constitution and that has acquired new contours and functions after the regulation of the 2015’s Procedure Code. The writ was originally designed to enforce the decision of the Superior Courts, or to ensure respect for the abstract judicial review. In the New Civil Procedure Code, the writ hypotheses are extended to also guarantee the mandatory precedents provided in article 988, CCP/2015. From the analysis of the historical-normative evolution of the institute, his legal nature, foundations and purposes, it will be demonstrated that is impossible to use the writ in a uniform way, considering that he has gradually distanced himself from traditional functions, be used to solve distinct problems that also require different solutions: the disrespect to what was decided in the concrete case, the disrespect to the decisions of judicial review and the lack of isonomy in the judgment of identical cases. Encouraged to bring practical solutions and usefulness to the writ, the study intends especially to answer how it can be adapted to guarantee the observance of the precedents.